Pengolahan Berbagai Produk Berbahan Baku Ikan pada Kelompok Mitra Desa Binaan UMI - Etik Prihatin; Muh. Haerdiansyah Syahnur (Penerbit Goodwood, 2021)
Purpose: The aim of designing this PkM is to increase and develop the potential and economic capacity of the community, particularly in the villages that have received assistance from the Universitas Muslim Indonesia, to improve the overall well-being of the community. It is necessary to achieve business independence while also opening up new employment opportunities for the family economy to undergo fundamental transformations. Another objective is to increase income and improve the well-being of rural communities during the period of recovery from the COVID-19 pandemic's economic impact. Method: The method is carried out by providing socialization to housewives who are members of the Family Empowerment group of partner villages, processing assistance to making products made from fresh fish produced from natural resources in Desa Padingging, Kabupaten Takalar. Results: The products are widely distributed, both in grocery stores backed by BUMDes and in traditional markets, as well as in the process of entering the Makassar souvenir shops that are characteristic of the city. Conclusions: To promote the use of natural resources in Takalar Regency, which is rich in natural resources and particularly abundant in fresh fish, socialization activities relating to their utilization have been carried out. This is done to maximize the economic potential currently available for the production of superior processed fish products. As a result of the activities that have been carried out, it is expected that housewives and partner villages supported by Universitas Muslim Indonesia will be able to earn a living independently.